Recycled Aggregates Production Through Economic Perspectives - Nitichote, Kirati; Wanchai Yodsudjai (International Journal of Sustainable Construction Engineering and Technology, 2022)
Construction and Demolition Waste (CDW), especially laboratory waste and concrete debris from construction, manufacturing errors, and demolition of existing structures, is posing challenges to the urbanization. As nowadays the aforementioned waste is disposed in landfills, this diminishes the development opportunity of cities. Although there are standards and research pointing out the application of recycled concrete aggregates in proper proportion, the theory has never been put into practice. This research aims to present feasibility of applying recycled aggregates through Bangkok’s economic perspectives. It is found that the investment in recycled aggregate plants takes nine years of payback period. Besides, the sensitivity analysis suggests that implementing certain strategies, such as imposing a landfill tax increase and applying dumping fee will significantly shorten the payback period of recycling business.